Astronaut Radiation Dose Calculation With a New Galactic Cosmic Ray Model and the AMS‐02 Data - Xuemei Chen; Songying Xu; Xiaojian Song; Ran Huo; Xi Luo (Space Weather)
Abstract We present a new calculation of the astronaut dose rate from the galactic cosmic rays in free space at 1 AU. We use the unshielded isotropic fluence‐to‐dose conversion coefficients given in the International Commission on Radiological Protection publication 123. A new 3D and time‐dependent solar modulation model based on Parker's transport equation as originally developed in Song et al. (2021, https://doi.org/10.3847/1538-4365/ac281c) is used to calculate the galactic cosmic ray spectra at 1 AU. This model uses the recent local interstellar spectra of Corti et al. (2019, https://doi.org/10.3847/1538-4357/aafac4), M. J. Boschini et al. (2020, https://doi.org/10.3847/1538-4365/aba901, 2021a, https://doi.org/10.3847/1538-4357/abf11c) to reproduce the PAMELA and AMS‐02 observations between 2006 and 2019. The radiation dose calculated from our model and from the AMS‐02 spectra in the same rigidity region agrees better than 1% for proton and helium in a time‐dependent way, and at 2% level for six most contributing cosmic ray elements averaged over 7 or 8.5 years. The time‐dependent dose rate analysis over 13 years shows an effective dose equivalent rate of 55–58 cSv/yr at solar minimum (January 2010) and 26 cSv/yr at solar maximum (February 2014).